FORMULATION CRACKERS PASTA TALAS (Colocasia esculenta) AND PURPLE SWEET POTATO (Ipomea batatas L) - Novidahlia, Noli; Amalia, Lia; Januarisca, Brida (JURNAL PERTANIAN, 2018)
Taro is rich in nutrients and purple sweet potato is rich in anthocyanin which can be functioned as a pigment. The aims of the study were to determine the best paste formulated using taro flour and mash sweet potato based on sensory quality test, to evaluate the preference level of crackers using hedonic test and to analyze the chemical properties of selected product. The study was begun with pasta preparation assigned by three ratios of taro flour and mash purple sweet potato (1:1 , 3:1 and 1:3). The sensory qualities of paste including color, taste, and texture were analyzed. Paste made with ratio of taro flour and mash purple sweet potato 1:3 had the best sensory qualities. The paste was then used for crackers making, crackers with filler of paste (sandwich) and crackers made by mixing the dough and paste. Each crackers was then evaluated its preference level using hedonic test including color, aroma, taste, crispyness, and the preferred crackers was analyzed its chemical properties including moisture, ash, protein, lipid, and carbohydrate. The results showed that sandwich crackers was preferred than mixed dough-paste crackers and contained of moisture 3.54%, ash 0.82%, protein 8.57%, fat 7.15%, and carbohydrates 79.93%.